Authority and responsibility of the Presidential Deputy in the Presidential Government System in Indonesia - Hadi Husodo Tjandra,; Sadjijono,; Slamet Suhartono,; Hufron, (Technium Social Sciences Journal, 2021)
The authority of the Vice President of the Republic of Indonesia isn’t strictly regulated in the constitution, even though the 1945 Constitution has undergone four changes. Even though in principle Indonesia has emphasized the adoption of a Presidential government system, by conducting direct elections for the President and vice president by the people in one pair as stipulated in Article 6A paragraph (1) of the 1945 NRI Constitution. This isn’t in accordance with the theory of state office which requires the existence of clarity of position, duties and authorities as well as accountability of state organs and philosophically considered unfair if later in carrying out their duties and obligations there is no proportional division of authority between the elected President and Vice President.